If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + 4) = 0 Reorder the terms: 2(4 + t) = 0 (4 * 2 + t * 2) = 0 (8 + 2t) = 0 Solving 8 + 2t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2t = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 2t = 0 + -8 2t = 0 + -8 Combine like terms: 0 + -8 = -8 2t = -8 Divide each side by '2'. t = -4 Simplifying t = -4
| 3(t+1)=-1+2(t-3) | | 12-7=56-21x | | 5(4s+4)=220 | | 5(45+4)=22 | | 5(45+4)=220 | | 6(2l+7)=78 | | (2-7j)(2+7j)= | | y^2-2y-5y+10= | | 4(a-4)=20 | | (V+4)*7=56 | | y=9x^2+36x-7 | | g(x)=4x-20 | | (q-10)*6=48 | | -(x+11)-4=7x+3 | | (e+4)*4=24 | | (x+6)(2x+5)=0 | | 9b-22=-18 | | 188+X=2279 | | 43-(-r)=15 | | 2b-(-2)=16 | | 1-(-2c)=-3 | | 3n-(-4)=19 | | 8x^7-5x^5+15x^4= | | 5x(2x-6)=-20 | | -7=3-2t | | 4s+9=12 | | -2r+-7=-6 | | 2q-8=2 | | 36+72+X=183 | | 3j+8=-10 | | 2j+7=4 | | 1=0t+.5*9.8*t*t |